2007
DOI: 10.1136/bjo.2006.108340
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile ocular blood flow: relationship with flow velocities in vessels supplying the retina and choroid

Abstract: POBF is associated with systolic and pulsatile components of blood flow velocities in both the CRA and the TSPCA. This result suggests that POBF determinations are influenced by the pulsatile components of both choroidal and retinal perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 18 publications
(19 reference statements)
3
22
1
2
Order By: Relevance
“…In such a case, a lower pulse amplitude at greater axial lengths would not necessarily imply reduced blood flow velocities within the retrobulbar bed, but it might be affected by variations in blood velocity at the central retinal artery. The work cited above by Zion and co-workers described a similar correlation between POBF and the central retinal artery pulse, which supports our findings [34].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In such a case, a lower pulse amplitude at greater axial lengths would not necessarily imply reduced blood flow velocities within the retrobulbar bed, but it might be affected by variations in blood velocity at the central retinal artery. The work cited above by Zion and co-workers described a similar correlation between POBF and the central retinal artery pulse, which supports our findings [34].…”
Section: Discussionsupporting
confidence: 92%
“…Several significant correlations resulted from the multivariate model, such as those between the pulsatile blood flow with the central retinal artery and ophthalmic artery blood velocities. Similar associations have been described in the past [34], and it has been suggested that the pulsations of the retrobulbar retinal circulation influence the POBF recordings. Correcting for the effect of axial length on the interactions between the three vascular beds resulted in the same correlations, with the exception of those between pulse amplitude and the ophthalmic artery, which did not exhibit any significance.…”
Section: Discussionmentioning
confidence: 54%
“…Low wall filter settings were used. To examine the OA, the sample volume was oriented nasally and superior to the optic nerve, OA is just lateral to and abuts the visible hyporeflective stripe representing the nerve, while the central retinal artery (CRA) was imaged in the shadow of the optic nerve, the sample volume was placed about 3 mm behind the surface of the optic disc 14. The Peak Systolic Velocity (PSV) and End Diastolic Velocity (EDV) values were obtained by taking the velocity reading at the peak of the spectral wave pattern and that at the wavetrough, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The bolus of blood entering the choroidal vasculature during systolic and diastolic phases transmits pressure to the anterior segment of the eye, affecting the OPA (Langham & To’Mey 1978; Silver & Farrell 1994). Recently, the pulsatility index of the choroidal vasculature was found to be strongly associated with OPA as measured by colour Doppler imaging (Zion et al. 2007).…”
Section: Introductionmentioning
confidence: 99%